Trends and determinants of clinical staff retention in the English NHS: a double retrospective cohort study - Moscelli, G; Nicodemo, C; Sayli, M; Mello, M (BMJ Publishing Group, 2024)
Objectives: To investigate how demographic, contractual and organisational factors are related to the retention of hospital workers in the English NHS. The study will specifically examine the trends in age-retention profiles. Design: A double retrospective cross-cohort study using administrative data on senior and specialty doctors, nurses and midwives who were included in the 2009 and 2014 payrolls of all English NHS hospital Trusts. These individuals were tracked over time until 2019 to examine the associations between sociodemographic characteristics and the retention of hospital workers in each cohort. Logistic regressions were estimated at the individual worker level to analyse the data. Additionally, a multilevel panel regression was performed using linked payroll-survey data to investigate the association between hospital organisation characteristics and the retention of clinical staff. Setting: Secondary acute and mental healthcare NHS hospital Trusts in England. Participants: 70 777 senior doctors (specialty and specialist doctors and hospital consultants) aged 30–70, and a total of 448 568 between nurses and midwives of any grade aged 20–70, employed by English NHS Trusts. Primary outcome measures: Employee retention, measured through binary indicators for stayers and NHS leavers, at 1-year and 5-year horizons. Results: Minority doctors had lower 1-year retention rates in acute care than white doctors, while minority nurses and midwives saw higher retention. Part-time roles decreased retention for doctors but improved it for nurses. Fixed-term contracts negatively impacted both groups’ retention. Trends diverged for nurses and doctors from 2009 to 2014—nurses’ retention declined while doctors’ 5-year retention slightly rose. Engagement boosted retention among clinical staff under 51 years of age in acute care. For nurses over 50, addressing their feedback was positively associated with retention. Conclusions: Demographic and contractual factors appear to be stronger predictors of hospital staff retention than organisational characteristics.